Influence of Education Level, Workload, and Remuneration System on Employee Performance at the Department of Transportation of Ngawi Regency - Sudaryono; Ahadiati Rohmatiah; Muhammad Imron (Citakonsultindo, 2026)
Public sector organizations, particularly in regional transportation, face strict market demands to adopt high standards of professionalism, speed, and operational efficiency. While employee performance is recognized as a dynamic outcome of complex internal and external factors, integrated studies concurrently examining the impact of intellectual capacity, operational pressure, and welfare guarantees remain limited. Therefore, this study aims to examine and analyze the partial and simultaneous influence of education level, workload, and remuneration system on employee performance at the Department of Transportation of Ngawi Regency, as well as to identify the most dominant variable. A causal quantitative approach was adopted, and a proportionate stratified random sampling technique was used to select a sample of 109 employees from a total population of 149 employees. Primary data was collected using a validated Likert scale questionnaire and analyzed using multiple linear regression via SPSS version 27. The hypothesis testing results demonstrated that education level and the remuneration system have a positive and significant effect on employee performance, whereas workload has a negative and significant effect. Simultaneously, education level, workload, and the remuneration system jointly have a significant effect on employee performance, explaining 74% of the performance variation (Adjusted R Square = 0.740). The dominant variable test revealed that the remuneration system is the factor with the strongest influence on employee performance. The study concludes that an equitable remuneration system is the most critical factor in maintaining work motivation and service quality among study participants. The study recommends that institutional leaders prioritize merit-based incentives, evaluate the distribution of daily workload, and continuously facilitate employee educational development to optimize public service performance